FRI0363 Do serum biomarkers of bone and OF cartilage degradation reflect structural damage in juvenile idiopathic arthritis (JIA)?. (23rd January 2014) - Pederzoli, S.; Malattia, C.; Cangemi, G.; Barco, S.; Pistorio, A.; Mazzoni, M.; Madeo, A.; Beltramo, A.; Lanni, S.; Beleva, D.; Consolaro, A.; Martini, A.
Abstract : Background: Serum biomarkers of bone and of cartilage degradation have been found to predict structural damage progression in Rheumatoid Arthritis (RA). Their potential value in JIA has never been explored. Objectives: To examine correlations between a panel of soluble biomarkers of bone and of cartilage degradation (C1-2C, CTX1) and joint damage as assessed by Conventional Radiography (CR) and Magnetic Resonance Imaging (MRI) in JIA Methods: The clinically more affected wrist of 62 JIA patients (female: 49, male:13, median age: 11.3 years, median disease duration: 4.1 years) was studied with CR (adapted Sharp-van der Heijde method and Poznanski score) and MRI (paediatric targeted and RA MRIs scores), coupled with standard clinical assessment. Forty-one patients had one-year imaging follow-up.Serum C1-2C, CTX1 were measured by ELISA assays in all JIA patients (N=62) and in gender- and age-matched healthy controls (N=140). Results: C1-2C and CTX1 levels did not significantly differ between JIA patients and healthy controls. Furthermore, C1-2C and CTX1 values in patients without radiological detected damage progression were comparable to those of the patients with radiographic progressive damage. Unexpectedly, as cross-sectional analysis, biomarkers of bone and of cartilage degradation did not significantly correlate with radiological structural damage. C1-2C was moderately correlated with physician's global assessment of disease activity (rs =0.42) and with CHAQ (rs =0.42). CTX1 was fairly correlated only with disease duration (rs =0.46).Baseline values of bone and of cartilage degradation did not predict structural damage progression at 1 year follow-up. Conclusions: Unlike adults with RA, C1-2C, and CTX1 do not seem to correlate with structural damage progression in JIA. The overlap in levels not only between patients and healthy controls but also between patients with progression and without progression significantly limits the clinical utility of these biomarkers. References: Syversen SW. Biomarkers in early rheumatoid arthritis: longitudinal associations with inflammation and joint destruction measured by magnetic resonance inaging and conventional radiographs. Ann Rheum Dis 2010, 69: 845-850 Disclosure of Interest: None Declared